2021
DOI: 10.1002/jcla.24132
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition on admission increases the in‐hospital mortality and length of stay in elder adults with acute ischemic stroke

Abstract: Stroke is one of the leading causes of increased disability-adjusted life-years 1 and the years of life lost. 2 Moreover, it is the second-leading cause of mortality worldwide, 3 with majority of these deaths occurring in low-income and middle-income countries. 4 China had a higher estimated global lifetime risk of stroke than that of the global average level (39.3% vs. 24.9%). 5 Although

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
(62 reference statements)
1
18
1
Order By: Relevance
“…All the studies applying the CONUT tool to stroke patients were carried out (since 2018) in Far Eastern Countries, with the exception of one from Spain [ 14 , 15 , 17 , 20 , 22 , 23 , 25 , 26 , 30 , 33 , 34 , 36 , 40 , 41 , 44 , 45 , 46 , 56 , 60 , 61 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], as reported in Table 1 . Stroke patients were classified according to the original four, but also in three (normal, light, and moderate/severe risk) or in two (absence or presence of risk) categories; a CONUT score ≥5 was commonly defined as the cut-off for a significant risk of malnutrition, but in two papers the cut-off was ≥2 [ 72 ] or ≥4 [ 23 ], respectively.…”
Section: Nutritional Screening Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies applying the CONUT tool to stroke patients were carried out (since 2018) in Far Eastern Countries, with the exception of one from Spain [ 14 , 15 , 17 , 20 , 22 , 23 , 25 , 26 , 30 , 33 , 34 , 36 , 40 , 41 , 44 , 45 , 46 , 56 , 60 , 61 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], as reported in Table 1 . Stroke patients were classified according to the original four, but also in three (normal, light, and moderate/severe risk) or in two (absence or presence of risk) categories; a CONUT score ≥5 was commonly defined as the cut-off for a significant risk of malnutrition, but in two papers the cut-off was ≥2 [ 72 ] or ≥4 [ 23 ], respectively.…”
Section: Nutritional Screening Toolsmentioning
confidence: 99%
“…Outcomes related to hospitalization and discharge have been considered by a few papers, showing that CONUT score/categories were associated with in-hospital mortality, LOS, infection, nutritional support, length of rehabilitation, and independence in ADL at discharge [ 17 , 26 , 33 , 70 , 72 ]. One study [ 26 ] evaluated AIS and an age-matched control group represented by hospitalized patients admitted to a hospital for disorders not related to acute stroke; it reported higher CONUT scores, higher in-hospital mortality, and longer LOS in AIS patients. In a convalescent ward, CONUT score was a predictor of the length of stay but not of changes in functional independence [ 30 ].…”
Section: Nutritional Screening Toolsmentioning
confidence: 99%
“…The prevalence of malnutrition in patients hospitalized for stroke ranges from 1.95% to 60.5%, depending on the assessment tool and diagnostic criteria [ 4 5 6 ]. Studies have reported that nutritional status at the time of stroke and traumatic brain injury affects the progress of acute-stage treatment [ 4 7 8 9 ]. Malnutrition during rehabilitation affects the progress of medical treatment and is associated with increased rates of mortality, readmission, and discharge to other institutions and higher medical costs [ 6 10 11 ].…”
Section: Prevalence Of Malnutrition In Patients With Neurological Dis...mentioning
confidence: 99%
“…To date, fewer studies have been produced about in-hospital short-term outcomes such as the LOS or 30-day re-admission rates in medical units. A recent monocentric Chinese study performed by Hao in 2022 demonstrated that a higher CONUT score predicts a higher LOS and in-hospital mortality, specifically in patients with ischemic stroke [ 24 ]; another recent, large multicenter retrospective study performed in China in older adults, collecting data from more than eleven thousand patients, demonstrated that a higher CONUT score predicts a longer LOS and in-hospital mortality in elderly patients [ 25 ]. However, similar studies concerning LOS or in-hospital mortality in more heterogeneous cohorts of patients or in Western countries are still lacking.…”
Section: Introductionmentioning
confidence: 99%